LOYALITAS PELANGGAN YANG DIPENGARUHI OLEH RESTAURANT SERVICE QUALITY YANG DIMEDIASI OLEH KEPUASAN PELANGGAN DAPUR DIPO PEKANBARU - Hamid Miftahurrahmi; Wijayanto Gatot; Restuti Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The importance of customer satisfaction in order to create loyalty (loyalty) to a product or service, the restaurant must be able to increase customer satisfaction with various strategies. The purpose of this study was to explain how Restaurant Service Quality affects customer loyalty with customer satisfaction as an intervening variable. This research was conducted in the city of Pekanbaru, Dapur Dipo Restaurant as the object of research. This study uses a quantitative approach with a sample of 110 respondents who are customers of the Dapur Dipo Restaurant. Sampling using non-probability sampling with purposive sampling technique. The research model iused a questionnaire and analyzed using SEM and PLS. The result of this study indicate that Restaurant Service Quality mediated by cutomer satisfaction has an effect on customer loyalty.Keywords: Restaurant Service Quality, Customer Satisfaction, Customer Loyalty